Altered lower extremity joint mechanics occur during the star excursion balance test and single leg hop after ACL-reconstruction in a collegiate athlete. Issue 4 (12th March 2018) - Samaan, Michael A.; Ringleb, Stacie I.; Bawab, Sebastian Y.; Greska, Eric K.; Weinhandl, Joshua T.
Abstract: The effects of ACL-reconstruction on lower extremity joint mechanics during performance of the Star Excursion Balance Test (SEBT) and Single Leg Hop (SLH) are limited. The purpose of this study was to determine if altered lower extremity mechanics occur during the SEBT and SLH after ACL-reconstruction. One female Division I collegiate athlete performed the SEBT and SLH tasks, bilaterally, both before ACL injury and 27 months after ACL-reconstruction. Maximal reach, hop distances, lower extremity joint kinematics and moments were compared between both time points. Musculoskeletal simulations were used to assess muscle force production during the SEBT and SLH at both time points. Compared to the pre-injury time point, SEBT reach distances were similar in both limbs after ACL-reconstruction except for the max anterior reach distance in the ipsilateral limb. The athlete demonstrated similar hop distances, bilaterally, after ACL-reconstruction compared to the pre-injury time point. Despite normal functional performance during the SEBT and SLH, the athlete exhibited altered lower extremity joint mechanics during both of these tasks. These results suggest that measuring the maximal reach and hop distances for these tasks, in combination with an analysis of the lower extremity joint mechanics that occur after ACL-reconstruction, may help clinicians and researchers to better understand the effects of ACL-reconstruction on the neuromuscular system during the SEBT and SLH.